The income-labour nexus to analyse labour through the prism of structural change. Insights from rural Africa - (:unkn) unknown (My University, 2023)
In sub-Saharan Africa, unprecedented population growth and low economic diversification raise questions about the possible trajectories of national demo-economic transitions. This situation raises questions about labour transformations, which should be addressed through the prism of structural change. This chapter shows how a regulationist approach, if it makes certain adjustments to institutional forms, makes it possible to analyze the evolution of the modalities of labour mobilization in rural areas of Sub-Saharan Africa.
Keywords: African Research